2020
DOI: 10.1186/s13756-019-0663-7
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence survey of antimicrobial use and healthcare-associated infections in Belgian acute care hospitals: results of the Global-PPS and ECDC-PPS 2017

Abstract: Background:The point prevalence survey of healthcare-associated infections (HAIs) and antimicrobial use organized by the European Centre for Disease Prevention and Control (ECDC-PPS) and the Global Point Prevalence Survey of antimicrobial consumption (Global-PPS) were simultaneously performed in Belgian acute care hospitals in 2017. Methods: Belgian acute care hospitals were invited to participate in either the ECDC or Global-PPS. Hospital/ward/ patient-level data were collected between September-December 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
32
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 10 publications
(17 reference statements)
10
32
2
Order By: Relevance
“… 8 , 15 Other studies have shown a prevalence of 51.4%, 57.1% and 55.6% for antimicrobial use in three different hospitals in Ghana. 7 , 16 Findings from our study are similar to antibiotic use data reported from many African institutions, 17 , 18 but higher compared with reports in many reviews spanning several other regions. 19 , 20 We realized that the context in which antibiotics are prescribed in sub-Saharan Africa is similar and there is a consensus that antibiotic use in the sub-region is high.…”
Section: Discussionsupporting
confidence: 86%
“… 8 , 15 Other studies have shown a prevalence of 51.4%, 57.1% and 55.6% for antimicrobial use in three different hospitals in Ghana. 7 , 16 Findings from our study are similar to antibiotic use data reported from many African institutions, 17 , 18 but higher compared with reports in many reviews spanning several other regions. 19 , 20 We realized that the context in which antibiotics are prescribed in sub-Saharan Africa is similar and there is a consensus that antibiotic use in the sub-region is high.…”
Section: Discussionsupporting
confidence: 86%
“…High adherence of prescriptions to the standard treatment guidelines in the current study (84.0%) is similar to previous studies in South Africa (98.0%), Northern Ireland (72.0%-81.8%), Jordan (92.2%-92.7%), Brazil (76.5%-87.3%) and Belgium (76.6%). [23][24][25][26] In contrast to these findings, a study in Nigeria found low adherence, ranging from 0.3% to 7.2%. 22 The finding of high adherence in Mbeya ZRH (94.0%), in contrast to the 63.0% found in 2018 by another study in the same hospital, may be accounted for by the possibility of postsurvey sensitisation and/or awareness.…”
Section: Open Accessmentioning
confidence: 76%
“…In contrast to our findings, appreciable numbers of patients were managed based on laboratory Open access results in South Africa, Brazil and Belgium. [24][25][26] Therefore, to avert the empirical use of antibiotics in these referral hospitals, it is recommended that similar PSS be routinely conducted to assess the trend. Also, addressing hospital-based and/or individual-based factors hindering routine provision of this service in the context of the Tanzanian National Action Plan on AMR implementation is urgently needed.…”
Section: Open Accessmentioning
confidence: 99%
“…For Belgium, 2017 ECDC-PPS data have been integrated into the Global-PPS tool and therefore were also included in the Belgian dataset. 13 Patient-level data included patient characteristics, information on the prescribed antimicrobials and their indication, as well as a number of quality indicators such as guideline compliance. Survey data were entered and validated using a web application, developed by the University of Antwerp.…”
Section: Methodsmentioning
confidence: 99%